Survival of advanced melanoma patients treated with immunotherapy and targeted therapy: A real‐world study. Issue 10 (21st April 2021) - Yu, Su‐Yeon; Mckavanagh, Dan; McPherson, Ian; Walpole, Euan; Atkinson, Victoria; Hollingworth, Samantha
Abstract: Introduction: We aimed to examine the survival outcomes plus patient and treatment characteristics of advanced melanoma patients treated with first‐line immunotherapy (IT), targeted therapy (TT), and chemotherapy (CTH) and compare findings with information from pivotal trials for each therapy. Materials and Methods: We retrospectively reviewed the use of systematic IT, TT and CTH therapies in melanoma patients in four Queensland public hospitals. We estimated median duration of overall survival (OS) and survival rates (6 months, 1, and 2 years) using Kaplan–Meier methods. We compared our findings to those of clinical trials. Results: Five hundred three patients who met the inclusion criteria were divided into three groups based on the first‐line treatment: IT 232; TT 157; and CTH 114. OS was 18 months with IT (95% CI 13, 22); 12 months with TT (95% CI 8, 15); and 5 months with CTH (95% CI 5, 6). The demographic characteristics, treatment protocols, and durations for IT and TT were generally consistent with trials but fewer patients in our study had subsequent therapy than in the trials. The OS in our study was slightly lower than the OS reported in trials. Conclusion: The OS of novel cancer therapy in the real world was lower than seen in trials but is expected given these are patients who have a poorer prognosis. A future study could investigate the impact of prognostic factors on survival in the longer term. This study provides evidence that we can use routinely collected real‐world data to evaluate the effectiveness of checkpoint and kinase inhibitors in patients with advanced melanoma.